Institutional and organizational frameworks for dairy and beef cattle recording in Kenya: a review and opportunities for improvement - Kosgey, I.S.; Mbuku, S.M.; Okeyo Mwai, Ally; Amimo, Joshua O.; Philipsson, J.; Ojango, Julie M.K. (Cambridge University Press, 2011)
To facilitate livestock improvement in developing countries, records on animal populations and their various productivity levels are important. However, in these countries, livestock recording presents a huge challenge. This paper presents an outline of the historical developments and the current scenario in dairy and beef recording in Kenya, where a recording scheme has been in place since 1963, yet the productive potential of most animals in the country remains unknown. The paper brings into context the state of recording in relation to the potential for future developments in dairy and beef production within the country. Despite the enormous existing potential, low numbers of livestock records are captured due to multiple challenges, which include limited funding, lack of incentives to record, limited feedback on records, a fragmented organizational structure, poor infrastructure, limited numbers of skilled personnel and lack of supporting policies. Strategies to overcome the challenges and achieve more sustainable utilization of the existing livestock populations are discussed. Linking recording to key service providers within the livestock production sector could enhance data collection, processing and feedback to livestock producers. The quality of extension services provided must be improved in order to holistically support livestock production. Recent international regulations on the traceability of livestock products sold within different countries mean that unless Kenya implements a robust animal recording programme, the country will be locked out of markets for its livestock products.